Immigrant Students and the Swedish National Test in History - Alvén, Fredrik (Frontiers in Education, 2021)
In Sweden, immigrant students with a non-European background perform worse in school than students from the majority group. Research has so far focused on language problems, and political investments have been concentrated around developing immigrant students’ language because it is hard to manage school without a functional language. However, social science in school also rests on cultural understanding, which is difficult if you are not a part of the culture. This is certainly true for the subject of history, which has a strong tradition of fostering a historical nationalistic canon. By analyzing the items in the national test in history relative to how the immigrant students perform, this study investigates whether there are certain types of items that, on the one hand, discriminate against them and, on the other hand, work to their advantage. This is important knowledge if we want to be able to make fair and just assessments.